Identification of microRNAs in black tiger shrimp (Penaeus monodon) under acute low-salinity stress - Shi, Jianzhi; Jiang, Song; Yang, Qibin; Li, Yundong; Yang, Lishi; Huang, Jianhua; Jiang, Shigui; Zhou, Falin (Frontiers in Marine Science, 2024)
Salinity is a common abiotic stress in the culture of penaeid shrimp. Through post-transcriptional regulation of gene transcripts, microRNAs play an important role in the adaptation to stressful environment. However, the involvement of microRNAs in salinity stress response of shrimp remains unclear. In present study, the sequence and expression profile of microRNAs in the hepatopancreas of low-salinity treated P. donomon were obtained by the high-throughput sequencing technique. A total of 679 miRNAs were identified, including 167 miRNAs which were significantly differentially expressed after low-salinity exposure (P < 0.05). Remarkably, most of these miRNAs were downregulated, suggesting that a series of genes were activated to participate in stress response. In addition, 43 miRNAs differentially expressed at all treatment were selected as putative key modulators. Enrichment analysis of genes targeted by these miRNAs indicated that a network consists of nervous system, immune system and endocrine system played a crucial role in maintaining the homeostasis of P. donomon under low-salinity stress. These findings may help contribute to a better understanding of the mechanism that regulate salinity tolerance in shrimp and provide valuable genetic information for following studies.